2012
DOI: 10.5194/sd-14-18-2012
|View full text |Cite
|
Sign up to set email alerts
|

500,000 Years of Environmental History in Eastern Anatolia: The PALEOVAN Drilling Project

Abstract: International Continental Scientific Drilling Program (ICDP) drilled a complete succession of the lacustrine sediment sequence deposited during the last ~500,000 years in Lake Van, Eastern Anatolia (Turkey). Based on a detailed seismic site survey, two sites at a water depth of up to 360 m were drilled in summer 2010, and cores were retrieved from sub-lake-floor depths of 140 m (Northern Basin) and 220 m (Ahlat Ridge). To obtain a complete sedimentary section, the two sites were multiple-cored in order to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 19 publications
0
40
0
Order By: Relevance
“…1b) during the ICDP (International Continental Scientific Drilling Program) project PALEOVAN in summer 2010 Litt et al, 2012). Here we present data of the uppermost 3.87-41.72 m of the event-corrected composite record (mcblf-nE; depth scale, which excludes volcanic ash layers and mass flow deposits; Stockhecke et al, 2014a), representing the time span from 9.48-111.39 ka BP.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1b) during the ICDP (International Continental Scientific Drilling Program) project PALEOVAN in summer 2010 Litt et al, 2012). Here we present data of the uppermost 3.87-41.72 m of the event-corrected composite record (mcblf-nE; depth scale, which excludes volcanic ash layers and mass flow deposits; Stockhecke et al, 2014a), representing the time span from 9.48-111.39 ka BP.…”
Section: Methodsmentioning
confidence: 99%
“…However, the interpretation of δ 18 O bulk is complex as it can be influenced by a number of climate variables, such as air and water temperature, seasonality of precipitation, moisture source and precipitation-to-evaporation ratio. According to Litt et al (2012Litt et al ( , 2009) and Lemcke and Sturm (1997), the δ 18 O bulk values of carbonates at Lake Van are primarily controlled by evaporation processes. Furthermore, Kwiecien et al (2014) and Pickarski et al (2015) mention that changes in seasonal rainfall have a significant effect on lake water isotope values.…”
Section: Palynologymentioning
confidence: 99%
See 1 more Smart Citation
“…3) Previous studies at Lake Van (e.g., Kwiecien et al, 2014;Lemcke and Sturm, 1997;Litt et al, 2012Litt et al, , 2009Wick et al, 2003) have shown that the stable isotope signature of lake carbonates reflects the complex interaction between both regional climatic variables and local site-specific factors. Such climate variables are the moisture source, in this case the eastern Mediterranean Sea surface water and the storm trajectories coming from the Mediterranean Sea, as well as temperature changes.…”
Section: The Oxygen Isotopic Composition Of Lake Van Sedimentsmentioning
confidence: 99%
“…357 m water depth; Fig. 1) was collected during the ICDP drilling campaign (International Continental Scientific Drilling Program, www.icdp-online.org) PALEO-VAN in summer 2010 Litt et al, 2012). The ca.…”
Section: Ahlat Ridge Composite Recordmentioning
confidence: 99%